The impact of land finance dependence on green economic efficiency: evidence from China - Guo, Chunyu (Frontiers in Environmental Science, 2025)
China’s reliance on land finance poses challenges to green economic efficiency. This study examines how local governments’ land finance dependence affects green economic efficiency, using panel data from prefecture-level cities and a super-efficiency SBM model. Findings show that land finance dependence significantly reduces green economic efficiency, particularly in non-resource-based, environmentally protected, and urban agglomeration cities, by diverting fiscal resources to short-term development and increasing debt risks. Policy reforms are recommended to reduce land finance dependence and promote sustainable fiscal incentives.